Skip to content

4-3 Solving recurrences with a change of variables

Sometimes, a little algebraic manipulation can make an unknown recurrence similar to one you have seen before. Let’s solve the recurrence

T(n)=2T(n)+Θ(lgn)T(n)=2T(\sqrt{n})+\Theta(\lg n) (4.25)

by using the change-of-variables method.

a. Define m=lgnm=\lg n and S(m)=T(2m)S(m)=T(2^m). Rewrite recurrence (4.25) in terms of m and S(m)S(m).

b. Solve your recurrence for S(m)S(m).

c. Use your solution for S(m)S(m) to conclude that T(n)=Θ(lgnlglgn)T(n)=\Theta(\lg n\lg\lg n).

d. Sketch the recursion tree for recurrence (4.25), and use it to explain intuitively why the solution is T(n)=Θ(lgnlglgn)T(n)=\Theta(\lg n \lg\lg n).

Solve the following recurrences by changing variables:

e. T(n)=2T(n)+Θ(1)T(n)=2T(\sqrt{n})+\Theta(1).

f. T(n)=3T(n3)+Θ(n)T(n)=3T(\sqrt[3]{n})+\Theta(n).

a

S(m)=T(2m)=2T(2m)+Θ(m)=2T(2m/2)+Θ(m)=2S(m/2)+Θ(m)S(m)=T(2^m)=2T(\sqrt{2^m})+\Theta(m)=2T(2^{m/2})+\Theta(m)=2S(m/2)+\Theta(m)

b

mlogba=mf(m)=m=Θ(mlogba)S(m)=Θ(mlgm) \begin{aligned} m^{\log_{b}a}=m\cr f(m)=m=\Theta(m^{\log_{b}a})\cr S(m)=\Theta(m\lg m) \end{aligned}

c

T(n)=S(lgn)=Θ(lgnlglgn)T(n)=S(\lg n)=\Theta(\lg n\lg\lg n)

d

4-3.1

depth:lglgn+1\lg\lg n +1, leaves: 2lglgn2^{\lg\lg n}

The total cost over all nodes at depth ii,for i=0,1,,lglgn1i=0,1,\dots,\lg\lg n-1 is 2i12iΘ(lgn)=Θ(lgn)2^i\cdot \frac{1}{2^i}\Theta(\lg n)=\Theta(\lg n)

T(n)=2lglgnΘ(1)+i=0lglgn1Θ(lgn)=Θ(lgn)+lglgnΘ(lgn)=Θ(lgnlglgn) \begin{aligned} T(n) & =2^{\lg\lg n}\Theta(1)+\sum_{i=0}^{\lg\lg n-1}\Theta(\lg n)\cr & =\Theta(\lg n)+\lg\lg n\Theta(\lg n)\cr & = \Theta(\lg n\lg\lg n)\cr \end{aligned}

e

depth:lglgn+1\lg\lg n +1, leaves: 2lglgn2^{\lg\lg n}

The total cost over all nodes at depth ii,for i=0,1,,lglgn1i=0,1,\dots,\lg\lg n-1 is 2iΘ(1)=Θ(2i)2^i\cdot \Theta(1)=\Theta(2^i)

T(n)=2lglgnΘ(1)+i=0lglgn12iΘ(1)=Θ(lgn)+(2lglgn1)Θ(1)=Θ(lgn) \begin{aligned} T(n) & =2^{\lg\lg n}\Theta(1)+\sum_{i=0}^{\lg\lg n-1}2^i\Theta(1)\cr & =\Theta(\lg n)+(2^{\lg\lg n}-1)\Theta(1)\cr & = \Theta(\lg n)\cr \end{aligned}

f

S(m)=T(3m)=3T(3m/3)+Θ(3m)=3S(m/3)+Θ(3m)S(m)=T(3^m)=3T(3^{m/3})+\Theta(3^m)=3S(m/3)+\Theta(3^m).

mlogba=mlog33=mf(m)=3m=Ω(m2+logba)3f(m/3)=33m/3(1/3)f(m)S(m)=Θ(f(m))=Θ(3m)T(n)=S(log3n)=Θ(n) \begin{aligned} m^{\log_{b}a}=m^{\log_{3}3}=m\cr f(m)=3^m=\Omega(m^{2+\log_{b}a})\cr 3f(m/3)=3\cdot 3^{m/3}\leq (1/3)f(m)\cr S(m)=\Theta(f(m))=\Theta(3^m)\cr T(n)=S(\log_{3}n)=\Theta(n)\cr \end{aligned}